(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Home automation has experienced increased attention due to the growth of the introduction of communications technology. The Internet of Things (IoT) involves the use of the Internet to manage any of the household equipment and applications. as IoT technology hasn’t gained any traction in the market, existing-home automation systems haven’t met user expectations, unworkable interface and costly issues have created, and constrained the possibilities, and wireless range has proved to be too limiting This paper presents a cost-effective crossbred home automation system with a both simple and highly efficient user interface for smartphones and an as well as for laptops. The system, which they refer to as IOT based Home, takes advantage of the Internet of things and Artificial Intelligence algorithms to help homeowners monitor their home environments and control their devices over the Internet any time of the day or any place they’re located. different IoT systems are tied together using a single device (based) gateway (the NodeMCU) as a Wi-Fi-enabled bridge to collect data from various sensors and deliver it to the IO Cloud server there is no matter where they are accessing IFTTT software, users’ smartphones and computers are connected to the internet can pull the collected data from several sensors (color several; for this application in casual writing, reading, radio-frequency identification, ultrasonic, and temperature sensors) A relays set is applied to service nodes, such as the one used in home environments to interconnect circuits. The design of the system is flexible enough to allow for its use in home applications, as well as on-site facilities that can be connected via a control box for measuring and The IoT system is intended to be used in homes and businesses to automate and enhance both life-safety applications easily and can be expanded to include autonomous The Internet of Things can provide value, convenience, safety, and security to SH residents for a low investment and energy consumption is of great significance for Smart home devices.